2016
DOI: 10.1038/srep38755
|View full text |Cite
|
Sign up to set email alerts
|

Microneedles with Controlled Bubble Sizes and Drug Distributions for Efficient Transdermal Drug Delivery

Abstract: Drug loaded dissolving microneedles (DMNs) fabricated with water soluble polymers have received increasing attentions as a safe and efficient transdermal drug delivery system. Usually, to reach a high drug delivery efficiency, an ideal drug distribution is gathering more drugs in the tip or the top part of DMNs. In this work, we introduce an easy and new method to introduce a bubble with controlled size into the body of DMNs. The introduction of bubbles can prevent the drug diffusion into the whole body of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…The focus of this study is the simple method we developed to load more DNA vaccine into the needle region of MN patch compared with vacuum or centrifugation self-assembly DNA polyplex vaccine formation. Although there are studies presenting effective tip-loaded MN fabrication approaches already 32 , 33 , no one likes our approach which can concentrate the encapsulated DNA vaccine to the needle region of MNs and also form DNA polyplex vaccine in the MNs using one-step fabrication process. To clarify the improvement, we stained the loaded DNA vaccine for porcine circovirus Type 2 (pcDNA4-PCV2) using GelStar™ Nucleic Acid Gel Stain (Lonza Rockland, Inc., Rockland, ME, USA), during which green fluorescence was used to monitor the distribution of DNA vaccine in the MNs.…”
Section: Resultsmentioning
confidence: 99%
“…The focus of this study is the simple method we developed to load more DNA vaccine into the needle region of MN patch compared with vacuum or centrifugation self-assembly DNA polyplex vaccine formation. Although there are studies presenting effective tip-loaded MN fabrication approaches already 32 , 33 , no one likes our approach which can concentrate the encapsulated DNA vaccine to the needle region of MNs and also form DNA polyplex vaccine in the MNs using one-step fabrication process. To clarify the improvement, we stained the loaded DNA vaccine for porcine circovirus Type 2 (pcDNA4-PCV2) using GelStar™ Nucleic Acid Gel Stain (Lonza Rockland, Inc., Rockland, ME, USA), during which green fluorescence was used to monitor the distribution of DNA vaccine in the MNs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with microneedle patches of similar dimensions also showed them to be painless 30 . In previous studies, bubbles have been incorporated into microneedle patches to help localize drugs within microneedles, but not to enable rapid microneedle separation 49,50 . Previous studies have also developed patches for rapid microneedle separation, using methods requiring complex, multi-step fabrication 19,24,[51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…The mount pushed the MNs against a hard metal surface that was perpendicular to the axis of mount movement. Upon needle failure, the force unexpectedly declined; the ultimate force applied instantly before this decline was recorded as the force of MN failure 52,53 . Data are represented in Table 2 as the mean values (n = 3 ± SD).…”
Section: Formulation Of Non-medicated Polymeric Microneedles (Mns) Smentioning
confidence: 99%